KORUPSI DANA DESA DALAM PROYEK PEMBANGUNAN PARIT OLEH OKNUM PEJABAT DESA ; SUATU TINJAUAN KRIMINOLOGI - Rezki Oktoberi; Kasmanto Rinaldi (JOURNAL EQUITABLE, 2023)
Corruption is an act of abuse of power and trust by a person against a problem o r organization for personal benefit or gains. This study aims to determine the modes of corruption in village funds carried out by the village head. This research uses qualitative method and case study research type. The theory used in this res earc h is the theory Willingness and Opportunity to Corrupt. This theory explains that corruption can occur if there is an opportunity due to system weakness o r lac k o f supervision and desire driven by need or gre ed. From this problem, the researcher saw that there were several modes carried out by the village head due to the opportunity to carry out modes and desires that were driven by personal needs and the lack of supervision of village funds. Keywords: Mode Corruption; Village Head; Willingness and Opportunity to Corrupt.